KONSEP PENDIDIKAN ANAK DALAM AL-QUR’AN - Ridho, Abdul Rasyid (UIN Mataram, 2022)
Deviance and resistance are expressions that are vulnerable to occur in children, both with friends, family, and society in general. This happens when you don't take preventive and rehabilitative actions early on. So we need a step to overcome this problem, namely by understanding the concept of children's education contained in the Qur'an. because in the Qur'an comprehensively explains the steps and methods of good children's education. As it is stated in the Qur'an with Qurrata a'yun (descendants who soothe the heart) not children who are Zurriyatan Dhi'afan (weak descendants).